Relationship Between Different Types of Violence and Mental Health in High School Students From Northern Mexico - Esparza Del Villar, Óscar Armando (Journal of interpersonal violence, 2022)
Different types of violence have been present in Mexico but there have been few studies that have analyzed their relationship with mental health in adolescents, especially in cities with high rates of social violence. It is important to compare different violence types and their relationship with mental health since not all relationships are the same. It appears that social violence has a stronger relationship with mental health, and for this reason it receives more attention, but other types of violence have a stronger relationship and do not receive as much attention. Chihuahua has been one of the most violent states in Mexico, and Juarez has been the most violent city in the world in 2009 and 2010. The purpose of the study is to compare the relationship of different types of violence (social, cyberbullying, partner violence, and child abuse and neglect) with mental health indicators (depression, anxiety, stress, self-esteem, and paranoid thoughts). There were 526 high school students, from the cities of Juarez (n = 282) and Chihuahua (n = 244). The mean age was 16.5 (SD = 1.4) years and 50.6% reported being males. The relationships among the variables were analyzed using Pearson?s correlations and multiple linear regressions. Both cities that have experienced social violence like carjacking, kidnapping, and sexual assault, but they have very small or no relationships with mental health indicators. Other types of violence have stronger correlations. Our findings suggest that interventions should not focus only in preventing and dealing with social violence, but that other types of violence must also be addressed in adolescents.